The relationship between personality traits, motivation levels, and speaking performance among EFL learners - Aljuaid, Nouf Saleh (Penerbit Universiti Kebangsaan Malaysia, 2022)
Considering the importance of learners' characteristics in facilitating or hindering second language oral communication, two personality traits that have received a lot of attention from researchers are extroversion and introversion. However, their findings have been contradictory - some found that extroversion correlates significantly with speaking skills while others disconfirm this finding. This study aimed to examine the EFL introvert and extrovert learners' speaking performances across motivational levels. The sample comprised 75 female students from a science college whose English proficiency was at the elementary to pre-intermediate levels, the students were taking English as a compulsory subject. The author used the English Level Test by the British council to determine their levels, the EPQR-S questionnaire was used to identify their personality types, and the AMTB questionnaire was used to measure their motivational levels. Their speaking ability was determined by administering a speaking test. Descriptive and inferential statistics were extracted from the data by using SPSS. The two-way ANOVA revealed no significant differences in speaking results between highly motivated introverts and extroverts as well as between low motivated introverts and extroverts. This means that the personality traits do not play an essential role in the learners' speaking performance, suggesting that EFL learners can perform well in the oral test regardless of their personality types and motivation level. This paper concludes by calling for more research into this seemingly clear-cut link between extroversion/introversion and the oral ability of ESL/EFL learners by examining this link with another variable that could provide a more nuanced insight.